Blood flow restriction added to usual care exercise in patients with early weight bearing restrictions after cartilage or meniscus repair in the knee joint: a feasibility study - Thomas Linding Jakobsen; Kristian Thorborg; Jakob Fisker; Thomas Kallemose; Thomas Bandholm (Journal of Experimental Orthopaedics)
Abstract Purpose Blood flow restriction – low load strength training (BFR‐LLST) is theoretically superior to traditional heavy strength training when rehabilitating patients who cannot heavily load tissues following surgery. The main purpose of this study was to examine the feasibility of BFR‐LLST added to usual care exercise early after cartilage or meniscus repair in the knee joint. Methods We included 42 patients with cartilage (n = 21) or meniscus repair (n = 21) of the knee joint. They attended 9 weeks of BFR‐LLST added to a usual care exercise program at an outpatient rehabilitation center. Outcome measures were assessed at different time points from four (baseline) to 26 weeks postoperatively and included adherence, harms, knee joint and thigh pain, perceived exertion, thigh circumference (muscle size proxy), isometric knee‐extension strength, self‐reported disability and quality of life. Results On average, patients with cartilage or meniscus repair completed > 84% of the total BFR‐LLST supervised sessions. Thirty‐eight patients reported 146 adverse events of which none were considered serious. No decrease in thigh circumference or exacerbation of knee joint or quadriceps muscle pain of the operated leg was found in either group during the intervention period. Conclusions BFR‐LLST added to usual care exercise initiated early after cartilage or meniscus repair seems feasible and may prevent disuse thigh muscle atrophy during a period of weight bearing restrictions. Harms were reported, but no serious adverse events were found. Our findings are promising but need replication using a RCT‐design. Trial registration NCT03371901, preprint (open access): https://www.medrxiv.org/content/10.1101/2022.03.31.22272398v1